2023
DOI: 10.1007/s40520-023-02358-2
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Score: a REMS-based indicator for the prediction of incident fragility fractures at 5 years

Abstract: Background Accurate estimation of the imminent fragility fracture risk currently represents a challenging task. The novel Fragility Score (FS) parameter, obtained during a Radiofrequency Echographic Multi Spectrometry (REMS) scan of lumbar or femoral regions, has been developed for the non-ionizing estimation of skeletal fragility. Aims The aim of this study was to assess the performance of FS in the early identification of patients at risk for incident fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…When considering the precision and repeatability of the Fragility Score, the intra-operator variability is minimal (RMS-CV = 0.49% for lumbar spine and RMS-CV = 0.43% for femoral neck), as is the inter-operator variability (RMS-CV = 0.73% for lumbar spine and RMS-CV = 0.64% for femoral neck) [ 15 ]. This is thought to be due to the automated selection of the region of interest and has been borne out in a recent review of REMS with excellent agreement and accuracy reported [ 7 ].…”
Section: Rems Bmd Diagnostic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…When considering the precision and repeatability of the Fragility Score, the intra-operator variability is minimal (RMS-CV = 0.49% for lumbar spine and RMS-CV = 0.43% for femoral neck), as is the inter-operator variability (RMS-CV = 0.73% for lumbar spine and RMS-CV = 0.64% for femoral neck) [ 15 ]. This is thought to be due to the automated selection of the region of interest and has been borne out in a recent review of REMS with excellent agreement and accuracy reported [ 7 ].…”
Section: Rems Bmd Diagnostic Performancementioning
confidence: 99%
“…The use of Fragility Score to predict fracture risk has been tested in a prospective, 5-year follow-up study in 1989 Caucasian men and women [ 15 ]. The diagnostic performance to predict future major osteoporotic fractures (over the next 5 years) was good in both women (AUC = 0.811) and men (AUC = 0.780) (AUC = 0.809 in men and AUC = 0.780 in women after adjustment for age and BMI) [ 15 ].…”
Section: Fracture Predictionmentioning
confidence: 99%
“…The ultrasound signals backscattered from the bone structures are analyzed and the pattern compared with models of fractured and non-fractured patients. The resulting fragility score relates to bone microarchitecture and may improve fracture prediction [ 129 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown a good diagnostic agreement between the BMD values obtained using the REMS technique compared to the DXA method. Moreover, REMS assessment was characterized by good repeatability and adequate precision but it was also able to predict the risk of fragility fractures [15][16][17]. In addition, REMS technology seems to be able to overcome some limitations of DXA, such as the overestimation of BMD in the presence of artifacts, osteophytes and fractures, and also to provide bone qualitative information [18,19].…”
Section: Introductionmentioning
confidence: 99%